Good governance and government sector performance at Majlis Perbandaran Seberang Perai - Caroline, Jim (2015)
Good governance is a basic management principle to strengthen government administrations in partnership with stakeholders. This implies that government administrations shall continuously change and develop to a more open, transparent, accountable, equitable, cost-effective and responsive form of governance to gain trust from the public. This study intends as a guide to help personnel in the government sector to understand and apply common principles of good governance and performance at each level of the organization in order to bring about improvement. Through a quantitative approach, this study involved 1,890 staff from 15 departments of Majlis Perbandaran Seberang Perai (MPSP) aims to examine the relationship between good governance and performance. A total of 364 personnel responded to the survey. Analysis using software Statistical Package for Social Science (SPSS) version 20.0 has found five principles of good governance were significantly positive correlated with performance. Information and decision support was strongly correlated to the organizational performance while four other elements namely accountability, leadership, strategy management and performance monitoring and transparency were moderately correlated. A significant impact emphasized good governance principles are the key to enhance performance. It shows that good governance plays an important role in the allocation of resources and management staff to improve service delivery to the citizens. This will lead to building trust between government and citizen. A value added in the performance would also support and enhance the development and economy of the nation.